Determinan Foreign Investment Direct (FID) di Indonesia - Dian Safitri Koesoemasari; Ratna Khaerunnisa; Nirmala Nirmala (Majalah Imiah Manajemen & Bisnis, 2022)
The purpose of this study is to determine the effect of interest rate variables, labor wages and exchange rates on foreign direct investment in Indonesia. The population is a sub-sector registered on the Indonesian Investment Coordinating Board. The research sample was taken using purposive sampling method and determined 20 subsectors. The analytical tool used is multiple linear regression analysis. The results of the t-test of the interest rate variable showed significant negative, the labor wage variable had a significant positive effect and the exchange rate had a significant negative effect on foreign direct investment. The implication of this study is that the government needs to monitor and stabilize interest rates and exchange rates in order to optimize FDI in Indonesia. The government also needs to monitor wage fixing policies so as not to burden investors and increase FDI in Indonesia